Speed Finite Control Set Model Predictive Control of a PMSM fed by Matrix Converter - Formentini, Andrea; Trentin, Andrew; Marchesoni, Mario; Zanchetta, Pericle; Wheeler, Patrick (Institute of Electrical and Electronics Engineers, 2015)
This paper presents a new speed Finite Control Set Model Predictive Control (FCS-MPC) algorithm which has been applied to a Permanent Magnet Synchronous Motor (PMSM) driven by a Matrix Converter (MC). This method replaces the classical cascaded control scheme with a single control law that controls the motor currents and speed. Additionally, unlike classical MC modulation methods, the method allows direct control of the MC input currents. The performance of the proposed work has been verified by simulation studies and experimental results.